Analisis Indeks Kualitas Tanah Tipe Penggunaan Lahan Hutan Pinus pada Lahan Kering di Kabupaten Aceh Besar - Umar Husein Abdullah; Reza Salima; Mulyanti; Mukhlis; Sufardi (Postgraduate, University of Mataram, 2024)
This study aims to determine the analysis of soil quality index in pine forest land use type on dry land in Aceh Besar Regency. This research focused on several field observation points in the pine forest land use type area on dry land in Aceh Besar Regency. The soil quality index in the pine forest land use type in Aceh Besar Regency is included in the medium category. This is due to soil sampling on the inceptisol soil type in Aceh Besar Regency, which has characteristics of less fertile soil. Soils that have a high percentage of dust have a higher risk of erosion, because dust has a relatively small size so that it is easily washed away by surface flow. low C-organic content, high volume weight, pH H2O, K- exchangeable, P-available and low N-total. In the type of pine forest land use, special treatment is needed in the form of adding organic matter to the soil by fertilizing, reforesting pine plants and conducting drainage so as to reduce nutrient leaching in the top soil layer.